Evaluation of supraspinatus strengthening exercises based on fiber bundle architectural changes. (3rd May 2016) - Sachdeva, R.; Farthing, J. P.; Kim, S. Y.
Abstract : Supraspinatus strengthening is an integral part of rehabilitation programs. However, there is disparity regarding the best exercise. Thus, we investigated the effects of supraspinatus strengthening exercises on muscle fiber bundle architecture using real‐time ultrasound. Participants were randomized into full‐can (FC; n  = 12), empty‐can (EC; n  = 11, ) and prone horizontal abduction (PHA; n  = 11) groups and performed three sessions/week for 8 weeks. Each session involved four sets of exercise for weeks 1–4 and six sets for weeks 5–8 with eight repetitions/set. Images of supraspinatus were captured in 0° (relaxed) and 60° (contracted) glenohumeral abduction. Fiber bundle length (FBL), pennation angle, and muscle thickness were measured at beginning, mid, and end of training. Maximum isometric abduction strength was measured in full‐can, empty‐can, and prone horizontal abduction positions using a hand‐held dynamometer. FBL decreased after 4 weeks in FC [relaxed: Δ = −0.54 cm, P  = 0.001, d  = 0.92; contracted: Δ = −0.27 cm, P  = 0.008, d  = 0.27] and EC [relaxed: Δ = −0.59 cm, P  = 0.008, d  = 0.86; contracted: Δ = −0.36 cm, P  = 0.013, d  = 0.59], but not in PHA [relaxed: Δ = −0.11, P  = 0.121, d  = 0.31; contracted: Δ = −0.06 cm, P  = 0.486, d  = 0.13]. Strength increased significantly from week 4–8 only in PHA (Δ = +0.96 kg, P  = 0.004, d  = 0.47) when tested in prone horizontal abduction position. Maintenance of FBL with increased strength indicates prone horizontal abduction may be a better exercise to strengthen supraspinatus.